Asymmetric benchmarking in bank credit rating - Chung-Hua Shen; Yu-Li Huang; Iftekhar Hasan (Bank of Finland, 2012)
This study proposes an information asymmetry hypothesis to examine why bank credit ratings vary among countries even when bank financial ratios remain constant. Countries are divided among those with low and high information asymmetry. The former include high-income countries, those in North America and West Europe regions, and those with strong institutional environment quality, whereas the latter group possess the opposite characteristics. This study hypothesizes that the influences of financial ratios on ratings are enhanced in low information asymmetry countries but reduced in countries with high information asymmetry. The sample includes the long-term credit ratings issued by Standard and Poor's from 86 countries during 2002-2008. The estimated results show that the effects of financial ratios on ratings are significantly affected by information asymmetries. Countries wishing to improve the credit ratings of their banks thus should reduce information asymmetry.
URN:NBN:fi:bof-20140807134
Keywords: G21; G32; G38; 330; Bank rating; Financial ratio; Information asymmetry; Institutional quality